A multifunctional colorimetric sensor originating from a cadmium naphthalene diimide-based metal–organic framework: photochromism, hydrochromism, and vapochromism. Issue 25 (11th June 2021) - Zhang, Guoshuai; Fu, Chen; Zhang, Heyi; Zhang, Hong
Abstract : A new cadmium metal–organic framework with photocontrolled luminescence properties and multiple chromic properties was synthesized for used as a multifunctional colorimetric sensor and provide a new route to design functional MOFs. Abstract : A new cadmium metal–organic framework [Cd(IsoNDI)(ClO4 )·H2 O] n (ZH-102, IsoNDI = N, N ′-di(4-pyridylacylamino)-1, 4, 5, 8-naphthalene diimide) has been synthesized under solvothermal conditions and characterized systematically by elemental analyses, IR spectroscopy, powder X-ray diffraction, and thermogravimetric analyses. Single-crystal X-ray diffraction analysis reveals that ZH-102 exhibits a 2D structure similar to a 'safety fence' that further stacks into a 3D supramolecular network, which is constructed by bridging of Cd–IsoNDI with perchlorate (ClO4 − ) anions and intermolecular interaction. Owing to the presence of electron-deficient NDI moieties and the generation of IsoNDI radicals, ZH-102 displays reversible photochromic properties under irradiation and heating (120 °C) and photocontrolled luminescence properties. In particular, ZH-102 also exhibited vapochromic behavior for detecting amines. Moreover, the ZH-102 showed that excellent heat causes hydrochromism properties with a color change from deep yellow to coffee color when  heated at 200 °C. Therefore, ZH-102 possesses multiple chromic properties and could be used as a colorimetric sensor, which provides a new route to design functional MOFs.